Introduction: Cities on Paper: On the Materiality of Paper in Urban Planning. (March 2020) - Lee, Min Kyung; Weiss, Sean
This introduction to this special section, "Cities on Paper: On the Materiality of Paper in Urban Planning, " explores the vital role played by paper documents in the practice of urban planning linked to the shaping of modern cities in Europe and the United States during the nineteenth and twentieth centuries. This introductory essay considers recent literature on the materiality of paper to show the significance of examining the visual and written information transcribed on its surface in concert with assessing how it has been assembled, organized, reproduced, circulated, distributed, and archived. By exploring such uses of paper documents in urban planning practices, such cartography, arboriculture, maintenance, and the production and dissemination of expert knowledge, the five essays in this section demonstrate the relevance of the material culture of paper within the municipal and national bureaucracies that spearheaded dramatic urbanization campaigns in modern cities.